Reflecting Adult Education for Migrants: From What We Have Discussed to What We Have to Discuss - Kyoungjin Jang (Adult Education Research Conference, 2019)
The purpose of this study is to conduct a critical reflection of the assumptions embedded in adult migrant education discourse based on a transnational perspective on migration. I reviewed what has been discussed in individual, sociocultural, and subject matter-related contexts of adult migrant education.
Keywords: : adult migrant education; critical reflection; transnationalism; work and education